Retrospective systematic analysis of incidence and severity of COVID-19 reinfection - SHI Lei; XIN Shen; SUN Qin; WANG Yuan; LI Danni; LI Ke (Shanghai yufang yixue, 2023)
ObjectiveTo investigate the incidence and severity of COVID-19 reinfection.MethodsWe searched relevant studies on COVID-19 reinfection， including cohort study， case report， and cross-sectional study in PubMed， Embase， CNKI and Wanfang databases. Revman5.3.0 was used for statistical analysis.ResultsA total of 52 studies in 19 countries were included. These literatures showed moderate and high quality. Furthermore， the pooled incidence of COVID-19 reinfection was estimated to be 1.9%（95%CI： 0.9%‒4.7%， P<0.01）， pooled incidence of reinfection among medical workers in hospitals and staff in nursing home was 13.8%（95%CI： 4.8%‒34.2%， P<0.01）， and pooled incidence of critical reinfection was 17.3%（95%CI： 11.5%‒25.9%， P<0.01）.Sensitivity and publication bias analysis showed that the pooled incidence was stable and no publication bias was identified.ConclusionIncidence and severity of COVID-19 reinfection are both high. Although the prevention and control policy against COVID-19 has been adjusted in China， the public should pay attention to taking protective measures to avoid the reinfection.